In vitro corrosion-fatigue behavior of biodegradable Mg/HA composite in simulated body fluid - E. Ghazizadeh; A.H. Jabbari; M. Sedighi (Journal of Magnesium and Alloys, 2021)
Magnesium and its composites as biodegradable materials offer especial capabilities to be used as bio-absorbable implants. However, their poor corrosion and fatigue properties in the physiological environment can restrict their applications. In this study, corrosion-fatigue tests have been performed on the extruded magnesium and magnesium/hydroxyapatite (Mg/HA) composites in a high cycle regime. To produce the composites, pure magnesium was reinforced by 2.5 wt.% and 5 wt.% of hydroxyapatite submicron particles using an electromagnetic-mechanical stirring method and hot extrusion process. The experimental density measurement exhibits that the porosity increases in the extruded samples with more hydroxyapatite particles. To investigate the corrosion and corrosion-fatigue behavior of the specimens, simulated body fluid (SBF) was used during in vitro tests. The results of the potentiodynamic polarization corrosion test show that the composite with 2.5 wt.% of hydroxyapatite (Mg/2.5 wt.% HA) and the pure magnesium specimen exhibit the highest and the lowest corrosion resistance, respectively. Regarding the elemental mapping analysis of the corroded samples, this behavior could be due to the formation of strong phosphorus-calcium based layers on the composite surface. The results obtained from the mechanical tests indicate that Mg/5 wt.% HA offered the highest tensile and compressive yield strengths, as well as the most promising high cycle fatigue behavior. During the corrosion-fatigue test, the simultaneous effects of fatigue and corrosion damages led to a similar corrosion-fatigue behavior in both composites. The fracture surfaces of the corrosion-fatigue samples suggest that the cracks are initiated in the corroded regions of the samples surface, which reduces the crack initiation step and subsequently decreases the fatigue life. In comparison with the pure magnesium, both composites exhibit more promising corrosion and corrosion-fatigue behaviors with a significant fatigue life improvement in the physiological environment.